185 The Safety and Tolerability of Lumateperone 42 mg for the Treatment of Schizophrenia: A Pooled Analysis of 3 Randomized Placebo-Controlled Trials. (April 2020) - Kane, John M; Vanover, Kimberly E; Durgam, Suresh; Davis, Robert; Satlin, Andrew; Rowe, William; Mates, Sharon; Tamminga, Carol
Abstract: Introduction: Lumateperone (ITI-007) is in late-phase clinical development for schizophrenia. Lumateperone has a unique mechanism of action that modulates serotonin, dopamine, and glutamate neurotransmission. This pooled analysis of lumateperone in 3 randomized, double-blind, placebo-controlled studies was conducted to evaluate the safety and tolerability of lumateperone 42mg (ITI-007 60mg). Methods: Data were pooled from the 3 controlled late-phase studies of lumateperone 42mg in patients with acute exacerbation of schizophrenia. Safety assessments of all patients who received at least one dose of any treatment included treatment-emergent adverse events (TEAEs), changes in laboratory parameters, extrapyramidal symptoms (EPS), and vital signs. Results: The safety population comprised 1, 073 patients (placebo [n=412], lumateperone 42mg [n=406], risperidone [n=255]). TEAEs that occurred in the lumateperone 42mg group at a rate of ≥5% and twice placebo were somnolence/sedation (24.1% vs 10.0%) and dry mouth (5.9% vs 2.2%). Rates of discontinuation due to TEAEs with lumateperone 42mg (0.5%) were similar to placebo (0.5%) and lower than risperidone (4.7%). Mean change in weight and rates of EPS-related TEAEs were less for lumateperone 42mg and placebo patients than risperidone patients. Mean change from baseline in metabolic parameters were similar or smaller for lumateperone 42mg vs placebo. Mean changes were notably higher in risperidone patients vs lumateperone 42mg and placebo for glucose, cholesterol, triglycerides, and prolactin. Conclusion: In this pooled analysis, lumateperone 42mg showed good tolerability with potential benefits over risperidone for metabolic, prolactin, and EPS risks. The only TEAE that occurred in >10% of lumateperone patients was somnolence/sedation, which was impacted by morning administration; in subsequent studies that administered lumateperone in the evening, somnolence/sedation rates were markedly reduced. These results suggest that lumateperone 42mg may be a promising new treatment for schizophrenia. Funding Acknowledgements: Supported by funding from Intra-Cellular Therapies, Inc.